Quantification of photophobia in visual snow syndrome: A case-control study. (April 2020) - Eren, Ozan E; Ruscheweyh, Ruth; Straube, Andreas; Schankin, Christoph J
Objective: To quantify photophobia in visual snow syndrome (VSS), a debilitating migraine-associated visual disturbance manifesting with continuous "TV snow-like" flickering dots in the entire visual field and additional visual symptoms, such as photophobia. Methods: Photophobia was compared between 19 patients with VSS and 19 controls matched for age, sex, migraine and aura using the Leiden Visual Sensitivity Scale (L-VISS). Results: Patients with VSS had an increased L-VISS-score compared to matched controls [(22.2 ± 5.9 vs. 4.4 ± 4.8; ANOVA, factors VSS and comorbid migraine: Main effect for VSS (F = 100.70; p  < 0.001), but not for migraine (F < 0.01; p  = 1.00) or the interaction (F = 1.93; p  = 0.16)]. An L-VISS-score of 14 identified VSS with a sensitivity and specificity of 95% (Receiver Operating Characteristic analysis, 0.986 ± 0.014, p  ≤ 0.001). Conclusion: Patients with VSS suffer continuously from photophobia at a level similar to chronic migraineurs during attacks. Although migraine and VSS share dysfunctional visual processing, patients with VSS might be more severely affected.